Farmers' Suicide in India: Implications for Public Mental Health - Anindya Das (Int J Soc Psychiatry 2011 57: 21, 2011)
Farmers' suicide in India is a cause of concern and government figures, though conservative, predict an impending epidemic. Various measures to curb this calamity are being made in a piecemeal manner. Considering it as an issue of social and mental health concern, this article attempts to evaluate the situation based on the tenet that health and illness are the result of a complex interplay between bio-logical, psychological, social, environmental, economic and political factors. Thus in India the agrarian crisis, among other causes, has been largely debated as the major reason for the current state of farmers. It is important that (psychiatric) epidemiology and public mental health try to evolve mechanisms to understand and implement measures, and take this into consideration when attempting health promotion and prevention